2019
DOI: 10.3390/antibiotics8040184
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Sulbactam and Cephalosporins Plus Daptomycin Against Daptomycin-Nonsusceptible VISA and H-VISA Isolates: An In Vitro Study

Abstract: This study assesses the synergistic effect of the combination of cephalosporins and sulbactam with daptomycin against daptomycin-nonsusceptible, vancomycin-intermediate resistant Staphylococcus aureus (VISA) or heterogeneous vancomycin-intermediate S. aureus (h-VISA) isolates. The in vitro activity of daptomycin against daptomycin-nonsusceptible VISA/h-VISA isolates after adding cephalosporins with or without sulbactam was evaluated. The MIC of daptomycin against the VISA/h-VISA isolates was reduced after addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In an in vitro study by Lai et al, a 100% synergistic effect was observed after the addition of sulbactam to cefotaxime [ 23 ]. The addition of sulbactam led to the increased antimicrobial activity of β-lactam antibiotics to Acinetobacter baumannii , which is one of the leading infectious agents in the ICU [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study by Lai et al, a 100% synergistic effect was observed after the addition of sulbactam to cefotaxime [ 23 ]. The addition of sulbactam led to the increased antimicrobial activity of β-lactam antibiotics to Acinetobacter baumannii , which is one of the leading infectious agents in the ICU [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between the results of synergy studies reported by other investigators with various antibiotic combinations including daptomycin plus gentamicin have been discussed [ 31 , 32 , 33 ]. These discrepancies were documented even when checkerboard and time–kill assays were performed in the same laboratory [ 20 , 34 , 35 , 36 ]. Most likely, this may have resulted from the use of arbitrarily chosen antibiotic concentration ratios that usually do not match each other in different methods.…”
Section: Discussionmentioning
confidence: 99%